Digital Transformation of MSMEs Based on Participatory Mentoring in Tanjung Senang Village - Thifal Adly At Taufik; Setia Mei Anggraini; Maulidia Rahma Yani; Naufal Raffliansyah; Tri Annisa Nabila; Armando Aprianto Pandiangan; Fidelis Palma Angelika; Gita Paramita Djausal (PT. TAKAZA INNOVATIX LABS, 2026)
Digital transformation has become an important strategy for Micro, Small, and Medium Enterprises (MSMEs) to improve competitiveness and business sustainability in the digital economy era. However, many MSMEs in Tanjung Senang Village still experience limited digital literacy and low adoption of digital business platforms. This study aimed to analyze the implementation of participatory mentoring-based digital transformation for MSMEs through QRIS activation, Google Maps registration, and business banner creation. The study employed a participatory action research design with a qualitative-descriptive approach. The population consisted of MSMEs in Tanjung Senang Village, while the sample involved six target MSMEs assisted by 13 university students during the Community Service Program. Data were collected through observation, interviews, documentation, and program evaluation sheets. Data analysis was conducted descriptively using achievement percentages for each program indicator. The results showed that banner creation achieved 100%, Google Maps registration reached 66.7%, and QRIS activation reached 33.3%, with an overall program achievement of 66.7%. The study concludes that participatory mentoring effectively improves MSME digital readiness, business visibility, and technology adoption, although digital literacy and administrative readiness remain major challenges